2017
DOI: 10.12991/marupj.323286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pharmacist Recommendations for Chemotherapy-Related Problems in Diabetic Cancer Patients

Abstract: Drug related-problems pose additional worse outcomes in cancer patients treated with chemotherapy. A vital role of the clinical pharmacist is the detection and prevention of drugrelated problems. The provision of patient education is an important step to reduce and prevent drug-related problems during chemotherapy administration. The objective of this study was to assess the occurrence of drug-related problems and the importance of effective provision of patient education and appropriate recommendations by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This could be achieved through pharmacist involvement in patient education about preventing unnecessary and irrational use of antibiotics, promoting adherence to appropriate prescribing guidelines, decreasing demand on antibiotics for viral upper RTIs and increasing adherence to prescribed antibiotics. Previous studies revealed that pharmacist educational intervention appeared to improve public knowledge about proper and safe medication use with improved patient-related outcomes [37][38][39][40]. Furthermore, collaborative practices between pharmacists and physicians could curb the misuse of antibiotics and resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…This could be achieved through pharmacist involvement in patient education about preventing unnecessary and irrational use of antibiotics, promoting adherence to appropriate prescribing guidelines, decreasing demand on antibiotics for viral upper RTIs and increasing adherence to prescribed antibiotics. Previous studies revealed that pharmacist educational intervention appeared to improve public knowledge about proper and safe medication use with improved patient-related outcomes [37][38][39][40]. Furthermore, collaborative practices between pharmacists and physicians could curb the misuse of antibiotics and resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of this knowledge could lead to increased hospital admissions, increased morbidity and reduced patients' quality of life. [35][36][37] Hence, radiology unitbased clinical pharmacist role is essential in reviewing treatment plan, evaluating, minimising and getting more follow-up of side effects and in detecting other Drug-Related Problems (DRPs) to improve patient-related health outcomes. Therefore, for better implementation of CPSs, it is important to enhance the awareness and recognition of other healthcare professionals about the clinical pharmacist concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the significance of drug-related problems (DRPs) contributes to poor patient-and health-related outcomes and significantly increases the cost of healthcare services (Al-taie et al, 2016;Al-taie, Köseoğlu, 2019). However, such problems are now highly identified and avoided due to the active roles of pharmacists in providing proper education about medical conditions, rational use of medications, optimise medication adherence, monitoring drug regimens, adjusting drug therapy and optimising medication therapy (Izzettin et al, 2017). Thus, pharmacists have a broad spectrum of clinical responsibilities that ensure the accuracy and appropriateness of medication administration, pharmacotherapy management, provision of proper patient-related care and the promotion of good therapeutic outcomes for patients during the process of pharmaceutical care.…”
Section: Implications Of Health Care Providers By Physicians' and Pha...mentioning
confidence: 99%